Anaesthetic Management of a Case of Peritonsillar Abscess in a Patient with Complete Heart Block with Pacemaker - M., Dr. Amukthamalyada; G., Dr. Kavya K.; Krishnaaithal, Dr. Suresh (International Journal of Innovative Research in Medical Science, 2020)
We report a case of complete heart block patient with pacemaker in situ (VVI mode-ventricle paced sensed and inhibited) with anticipated difficult airway of a morbid obese patient presenting for incision and drainage of peritonsillar abscess on an emergency basis because of impending respiratory distress. The challenges encountered in this case was: Programming the pacemaker to asynchronous mode { VOO mode-ventricle paced, none sensed and no response to sensing) in this case} Managing difficult airway.